Perancangan Aplikasi Stok Barang Berbasis Web Pada Anugrah Tex - Hidayat Affyat, Ega; Nanang (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Anugrah Tex is a business that runs in the field of fabric or textile material distributors. The current system often has errors in inputting goods data so that the process of recording or making reports is hampered, therefore the need for a stock application. Stock application is a technology that can improve the efficiency of the stock management process and stock reports. This application was developed using the waterfall method, while PHP language is used as programming language and MySQL for the database. Based on the results of testing this application can increase employee efficiency in the process of inputting stock items and making stock reports so the employee can do better performance.